Elevating MHC I expression on tumor cells by nanovesicles loading tyrosine kinase inhibitors can improve the efficacy of cancer vaccines - Xie, Huimin; Ma, Lin; He, Xiaoli; Zhao, Songsong; Wang, Jin; Zhu, Ao; Liu, Changming; Piskareva, Olga; Deng, Chao; Meng, Fenghua; Liu, Mi (Frontiers in Immunology, 2025)
IntroductionCancer vaccines work through activating tumor-specific T cells, which can specifically attack cancer cells by recognizing antigens binding with Major-Histocompatibility-Complex I (MHC I) molecules. The downregulation or loss of MHC I expression on tumor cells can affect the efficacy of cancer vaccines.MethodsHerein, to increase the MHC I expression on tumor cells, a nanovesicle-based strategy was developed to improve the efficacy of  cancer vaccines. Several clinically applied medicines, such as tyrosine kinase inhibitors (TKIs), were screened for their capacity to upregulate MHC I.ResultsTwo TKIs, Sunitinib and Sorafenib, were found to be very effective in elevating MHC I expression, and they were encapsulated into redox-responsive nanovesicles respectively (SUN-KD10 or SOR-KD10), which demonstrated favourable tumor-targeting capabilities in the tumor microenvironment. Sunitinib or Sorafenib activates the IFNγ/STAT1 pathway, which improve the expression of MHC I. When combined with whole-tumor-antigen-loaded nanovaccines, these nanovesicle formulations elicited a synergistic antitumor effect in both breast cancer and melanoma mouse models. The tumors in the tumor-bearing mice treated with combined strategy grew more slowly and the survival times of such mice are significantly prolonged.DiscussionThe studies demonstrated that more tumor-specific T cells were activated in the combined strategy treated mice, suggesting improved immune-mediated tumor clearance. This combinatorial approach provides a promising strategy to overcome immune evasion and to enhance the therapeutic outcomes of cancer vaccine-based immunotherapy by using clinical-applied medicines with cancer vaccines.